Vessel Form and Function in the Ceramic Assemblages from Bilbao and Santa Lucia Cotzumalhuapa, Guatemala - (:unkn) unknown (My University, 2013)
My investigation of two ceramic assemblages from Santa Lucia Cotzumalhuapa in the Guatemala piedmont zone builds on previous ceramic studies; however, my research focuses on vessel form and decoration as possible indicators related to human activity and site development in the region. I compared data from the Pacific Coast Archaeological Project Relational Database (2002), which include type names, vessel forms, dimensions, and contextual information, with Parsons' findings from the Milwaukee Public Museum Bilbao Project (1967). My quantitative analysis focused on functional vessel attributes related to ceramic types, forms, and decorations from the Santa Lucia Cotzumalhuapa ceramic assemblages to examine the waxing and waning of trends over time, to infer the possible function of the ceramics, and to formulate hypotheses about the social and ritual uses of these objects. Beginning in the Formative (1150 - 250 BC), both assemblages have limited vessel forms and sherds frequencies but, later during the Middle and Late Classic (AD 200-600), pottery becomes more diverse in vessel form types and sherd frequencies increase. This shift in pottery production corresponds with a major phase of construction in the Cotzumalhuapa region, influence from regional sites along the Pacific coast, piedmont, and highlands areas, and a change from household pottery production to craft specialization.
Keywords: Guatemala; Pottery